Genotyping of a Clinically Important SNP rs1799853 Present in the CYP2C9 Gene Using Tetra-primer ARMS PCR Method - Tahsin, Anika (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology 2020.